Dislocation of hemiarthroplasty after hip fracture is common and the risk is increased with posterior approach: result from a national cohort of 25,678 individuals in the Swedish Hip Arthroplasty Register - Ammar Jobory; Johan Kärrholm; Susanne Hansson; Kristina Åkesson; Cecilia Rogmark (Acta Orthopaedica, 2021)
Background and purpose — Reported revision rates due to dislocation after hemiarthroplasty span a wide range. Dislocations treated with closed reduction are rarely reported despite the fact that they can be expected to constitute most of the dislocations that occur. We aimed to describe the total dislocation rate on the national level, and to identify risk factors for dislocation. Patients and methods — We co-processed a national cohort of 25,678 patients in the Swedish Hip Arthroplasty Register, with the National Patient Register (NPR) and Statistics Sweden. Dislocation was defined as the occurrence of any ICD-10 or procedural code related to hip dislocation recorded in the NPR, with a minimum of 1-year-follow-up. In theory, all early dislocations should thereby be traced, including those treated with closed reduction only. Results — 366/13,769 (2.7%) patients operated on with direct lateral approach dislocated, compared with 850/11,834 (7.2%) of those with posterior approach. Posterior approach was the strongest risk factor for dislocation (OR = 2.7; 95% CI 2.3–3.1), followed by dementia (OR = 1.3; CI 1.1–1.5). The older the patients, the lower the risk of dislocation (OR = 0.98 per year of age; CI 0.98–1.0). Neither bipolar design nor cementless stems influenced the risk. Interpretation — The choice of posterior approach and dementia was associated with an increased dislocation risk. When hips treated with closed reduction were identified, the frequency of dislocation with use of direct lateral and posterior approach more than doubled and tripled, respectively, compared with when only revisions due to dislocation are measured.